Experimental and numerical investigations of the jaw crusher supporting structure fatigue failure - Rusiński, Eugeniusz (Strojniški vestnik, 2013)
In the paper investigations of the causes of fatigue cracks of the jaw crusher supporting structure are presented. The problems have appeared after short time of operation of the new crushing facility. A lot of fatigue cracks with high growth rate and bolts failures were observed in the crusher supporting structure. Considering high dynamic forces, which occur during operation of such equipment it was decided to investigate the problem to prevent catastrophic failure of the crushing station. A specially developed, combined numerical and experimental method was used to find out the reasons and to solve the problem.
Keywords: čeljustni drobilniki; dinamična trdnost; eksperimentalne metode; experimental methods; fatigue resistance; jaw crushers; numerical simulations; numerična simulacija; resonanca; resonance